Analisis Keabsahan Perjanjian Jual Beli Dengan Hak Membeli Kembali Dan Implikasi Hukumnya Terhadap Pembatalan Akta Notaris (Studi Putusan Kasasi Nomor 2491 K/Pdt/2025) - Nirmolo, Dessy Pintoko (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
A sale and purchase agreement with the right of repurchase is regulated under the Indonesian Civil Code; however, in practice, it is often used to disguise a loan agreement. This study aims to analyze the validity of such agreements and their legal implications for the annulment of notarial deeds based on Supreme Court Decision Number 2491 K/Pdt/2025. This research employs a normative juridical method with statutory and case approaches. The findings indicate that the Supreme Court assessed the validity of the agreement not merely from its formal requirements and authentic deed form, but from the substantive legal relationship between the parties. An agreement that essentially constitutes a loan relationship but is framed as a sale and purchase with the right of repurchase is deemed null and void due to the absence of a lawful cause and its contradiction with the principle of good faith. The annulment of the notarial deed in this case was not due to formal defects, but to substantive defects in the content of the agreement. This decision emphasizes the importance of prudence by notaries in reflecting the true intent of the parties to ensure legal certainty and prevent legal evasion.